Immortalizing the immortals: understanding the needs of the UP College of Fine Arts Library towards the development of an archives management program for their national artist for visual arts collections - Nardo, Albert Joriz V.
The UP College of Fine Arts, the oldest arts and design educational institution in the Philippines, currently houses multiple archival collections of some of the National Artist for Visual Arts. This study analyzes the needs of the institution in order to establish an archives management program that allows these collections to be imparted to the memory processes of the users. To determine these, the researcher conducted a stakeholder analysis with the college head librarian and the college student council representative. Results show that in order to implement an efficient and effective program, the institution needs various policies and plans regarding appraisal, acquisition, arrangement, access, promotion, and emergency situations; and additional archives and records management training for the library staff and administrator; and additional staff members and facilities. This study highlights the importance of analyzing various stakeholders in order to determine the appropriate needs of an institution to prepare them in giving efficient and effective archival services, which in turn would ensure that the information contained within the confines of the archival facility would become part of the memory processes of the potential users and would allow the immortals of Philippine Visual Arts to influence, inspire, and educate the current and future generations of researchers.